Knowledge and attitude on epilepsy among neurology patients and their attendants: Mixed methods research at a tertiary hospital - S. Ramesh Kannan; R. Rajalakshmi; Varun Babu; Kandasamy Ravichandran (Journal of Current Research in Scientific Medicine)
Background: Epilepsy is a recurrent and common neurological disorder with less awareness about epilepsy among the public. Sociocultural attitudes have a role to play in epilepsy management. This could be due to misconceptions of the public on witnessing an epileptic seizure. Hence, the current study evaluated knowledge, attitude, and perception of neurology outpatient department and inpatients and their caregivers, at the tertiary care hospital in South India. Materials and Methods: A mixed methods research with a single hospital-based, cross-sectional, quantitative study and the phenomenological type of qualitative study with focused group discussion were performed. A purposive sampling technique was used to select a total of 140 participants for the quantitative study using the Public Attitudes toward Epilepsy questionnaire. Results: Among 140 participants, although 80% have heard of epilepsy through witnessing the episode or mass media, 42% were unaware of it. Seventy percent do not know about triggering factors, or measures to prevent injury during epilepsy and 55% do not know the first aid measures. Forty-nine percent had an unfavorable attitude about epilepsy. Thirty-eight percent of the participants still believe that epilepsy is a kind of insanity. Only 48% believe that person with epilepsy can have a normal life like others. Conclusion: Knowledge and attitude toward epilepsy have improved, however, it is found to be low despite increased literacy rate and access to technology. Community-based health educational campaigns by medical fraternities will be beneficial to alleviate negative attitudes and improve knowledge about epilepsy among the public.